Inside the Hollywood Fan Magazine : A History of Star Makers, Fabricators, and Gossip Mongers - Slide, Anthony (Book collections on Project MUSE., 2010)
"The fan magazine has often been viewed simply as a publicity tool, a fluffy exercise in self-promotion by the film industry. But as an arbiter of good and bad taste, as a source of knowledge, and as a gateway to the fabled land of Hollywood and its stars, the American fan magazine represents a fascinating and indispensable chapter in journalism and popular culture." "Anthony Slide's Inside the Hollywood Fan Magazine provides the definitive history of this artifact. It charts the development of the fan magazine from the golden years when Motion Picture Story Magazine and Photoplay first appeared in 1911 to its decline into provocative headlines and titillation in the 1960s and afterward. Slide discusses how the fan magazines dealt with gossip and innuendo and how they handled nationwide issues such as Hollywood scandals of the 1920s, World War II, the blacklist, and the death of President Kennedy. Fan magazines thrived in the twentieth century, and they presented the history of an industry in a unique, sometimes accurate, and always entertaining style." "This major cultural history includes a new interview with 1970s media personality Rona Barrett, as well as original commentary from a dozen editors and writers. Also included is a chapter on contributions to the fan magazines from well-known writers such as Theodore Dreiser and e. e. cummings. The book is enhanced by an appendix documenting some 268 American fan magazines and including detailed publication histories, This appendix is supplemented by listings of British fan magazines and fan club journals, making much of this historical information available for the first time."--BOOK JACKET.